Specific transport of 3‐fluoro‐l‐α‐methyl‐tyrosine by LAT1 explains its specificity to malignant tumors in imaging. Issue 3 (19th February 2016) - Wei, Ling; Tominaga, Hideyuki; Ohgaki, Ryuichi; Wiriyasermkul, Pattama; Hagiwara, Kohei; Okuda, Suguru; Kaira, Kyoichi; Oriuchi, Noboru; Nagamori, Shushi; Kanai, Yoshikatsu
Abstract : 3‐ 18 F‐l ‐α‐methyl‐tyrosine ([ 18 F]FAMT), a PET probe for tumor imaging, has advantages of high cancer‐specificity and lower physiologic background. FAMT‐PET has been proved useful in clinical studies for the prediction of prognosis, the assessment of therapy response and the differentiation of malignant tumors from inflammation and benign lesions. The tumor uptake of [ 18 F]FAMT in PET is strongly correlated with the expression of L‐type amino acid transporter 1 (LAT1), an isoform of system L upregulated in cancers. In this study, to assess the transporter‐mediated mechanisms in FAMT uptake by tumors, we examined amino acid transporters for FAMT transport. We synthesized [ 14 C]FAMT and measured its transport by human amino acid transporters expressed in Xenopus oocytes. The transport of FAMT was compared with that ofl ‐methionine, a well‐studied amino acid PET probe. The significance of LAT1 in FAMT uptake by tumor cells was confirmed by siRNA knockdown. Among amino acid transporters, [ 14 C]FAMT was specifically transported by LAT1, whereasl ‐[ 14 C]methionine was taken up by most of the transporters. Km of LAT1‐mediated [ 14 C]FAMT transport was 72.7 μM, similar to that for endogenous substrates. Knockdown of LAT1 resulted in the marked reduction of [ 14 C]FAMT transport in HeLa S3 cells, confirming the contribution of LAT1 in FAMT uptake by tumor cells. FAMT is highly specific to cancer‐type amino acid transporter LAT1, which explains the cancer‐specific accumulation of [ 18 F]FAMT in PET. This, vice versa, further supports the cancer‐specific expression of LAT1. This study has established FAMT as a LAT1‐specific molecular probe to monitor the expression of a potential tumor biomarker LAT1. Abstract : In this study, to assess the transporter‐mediated mechanisms in FAMT uptake by tumors, we have synthesized [14C]FAMT for in vitro transport assay and revealed that FAMT is very specific to cancer type amino‐acid transporter LAT1 and not transported by any other amino acid transporters. This explains cancer‐specific accumulation of [18F]FAMT in PET.